The Herodotus Paradox - Michael R. Baye; Dan Kovenock; Casper G. de Vries (Tinbergen Institute, 2010)
The Babylonian bridal auction, described by Herodotus, is regarded as one of the earliest uses of an auction in history. Yet, to our knowledge, the literature lacks a formal equilibrium analysis of this auction. We provide such an analysis for the twoplayer case with complete and incompete information, and in so doing identify what we call the Herodotus Paradox.
Keywords: C72; D44; 330; second price; transfer to loser; Auktionstheorie; Unvollkommene Information; Gleichgewicht; Theorie